Green Process: Improved Semi-Continuous Fermentation of Pichia pastoris Based on the Principle of Vitality Cell Separation - Wang, Denggang; Li, Wenjie; Zhang, Xinying; Liang, Shuli; Lin, Ying (Frontiers in Bioengineering and Biotechnology, 2021)
he large-scale fermentation of Pichia pastoris for recombinant protein production would take a long production period and produce a large amount of waste yeast, which separation costs are relatively high for the ultrahigh cell density. A novel semi-continuous fermentation of P. pastoris could be separated vitality cells from broth and recycle the cell to produce high secretory recombinant pectate lyase, based on the principle of the difference of cells sedimentation coefficients with the formation of salt-bridges between the metal ions and various cell states. Compared with batch fed-cultivation and general semi-continuous culture, the novel semi-continuous processes presented significant advantages, such as consumed fewer resources, less time cost, and produced less waste yeast. With the sedimentation of Pichia pastoris by Fe3+ metal ions addition, the optimized semi-continuous fermentation only consumed 14.8±0.0% glycerol, 97.8±1.3% methanol, 55.0±0.9 inorganic salts, 81.5±0.0% time cost, and 77.0±0.1% waste yeast emission of batch fed-cultivation to produce the equal amount of proteins, and the cost of solid-liquid separation was lower for cells in the collected fermentation broth. Due to economic and green efficiency, the novel process could potentially be validly used Pichia pastoris to produce recombinant proteins.